Biomechanical and biochemical assessment of YB-1 expression in A375 melanoma cell line: Exploratory study - Cykowska, Anna; Hofmann, Ulf Krister; Tiwari, Aadhya; Kosnopfel, Corinna; Riester, Rosa; Danalache, Marina (Frontiers in Molecular Medicine, 2023)
Malignant melanoma is the most lethal form of skin cancer. Y-box binding protein 1 (YB-1) plays a prominent role in mediating metastatic behavior by promoting epithelial-to-mesenchymal transition (EMT). Migratory melanoma cells exhibit two major migration modes: elongated mesenchymal or rounded amoeboid. Using A375 melanoma cell line and the YB-1 knock-out model, we aimed to elucidate biochemical and biomechanical changes in migration signaling pathways in the context of melanoma metastases. We subjected A375 YB-1 knock-out and parental cells to atomic force microscopy (stiffness determination), immunolabelling, and proteome analysis. We found that YB-1 expressing cells were significantly stiffer compared to the corresponding YB-1 knock-out cell line. Our study demonstrated that the constitutive expression of YB-1 in A375 melanoma cell line appears to be closely related to known biomarkers of EMT, nestin, and vimentin, resulting in a stiffer phenotype, as well as a wide array of proteins involved in RNA, ribosomes, and spliceosomes. YB-1 knock-out resulted in nestin depletion and significantly lower vimentin expression, as well as global upregulation of proteins related to the cytoskeleton and migration. YB-1 knock-out cells demonstrated both morphological features and biochemical drivers of mesenchymal/ameboid migration. Melanoma is a highly plastic, adaptable, and aggressive tumor entity, capable of exhibiting characteristics of different migratory modes